The Multifaceted Roles of Myrrha in the Treatment of Breast Cancer: Potential Therapeutic Targets and Promises - Anwar Shams MD, MSc, PhD; Abdullah Ahmed Alzahrani; Taghreed A Ayash MSc, PhD; Shadi Tamur MD, FRCPC, FAAP; Majed AL-Mourgi MD, FRCS, FCCP, FACS (Integrative Cancer Therapies)
Background: Breast cancer is a critical threat to human health, and effective targeted agents showing lower systemic toxicity are still lacking. Therefore, exploring new potent therapeutic candidates with a broader safety margin is warranted. Alternative medicine, which has historically been used in traditional Chinese medicine, has played an increasingly prominent role in this area of research. This study introduces Commiphora myrrha (or myrrh) as a potential therapeutic candidate for treating breast cancer patients. Myrrh bioactive extracts have been used traditionally for decades to treat numerous medical disorders, including cancers, specifically breast cancer. Nonetheless, myrrh’s precise rudimentary mechanisms of action in regulating genes involved in breast cancer evolution and progression remain elusive. Purpose: Herein, we use a network pharmacology platform to identify the potential genes targeted by myrrh-active molecules in breast cancer. Method: The identified targets’ expression profiles were determined at the mRNA and protein levels using The Breast Cancer Gene-Expression Miner v5.0 (bcGen-ExMiner v5.0) and The Human Protein Atlas datasets, respectively. A gene signature composed of the specifically designated genes was constructed, and its association with different breast cancer molecular subtypes was investigated through the Gene expression-based Outcome for Breast Cancer (GOBO) online tool. The protein mapping relationship between potential myrrh targets and their partner proteins during breast cancer development was screened and constructed through the STRING and ShinyGO databases. In addition, the Kaplan-Meier plots (KM-plot) prognostic tool was applied to assess the survival rate associated with the expression of the current gene signature in different human cancers, including breast cancer. Results: Combining the results of network pharmacology with other bioinformatics databases suggests that myrrh’s active components exert anti-cancer effects by regulating genes involved in breast cancer pathogenesis, particularly PTGS2, EGFR, ESR2, MMP2, and JUN. An individual evaluation of the expression profiles of these genes at both mRNA and protein levels reveals that a high expression profile of each gene is associated with breast cancer advancement. Moreover, the GOBO analysis shows an elevated expression profile of the PTGS2/ESR2/EGFR/JUN/MMP2 genes’ signature in the most aggressive breast cancer subtype (Basal) in breast tumor samples and breast cancer cell lines. Furthermore, the STRING protein interaction network and the KEGG analyses indicate that myrrh exerts therapeutic effects on breast cancer by regulating several biological processes such as cell proliferation, cell migration, apoptosis, and various signaling pathways, including TNF, PI3K-Akt, NF-κB, and MAPK. Consistently, breast cancer patients with high expression of this genes’ signature display poor survival outcomes. Conclusions: The present study is the first attempt to explore the biological involvement of myrrh-targeted genes during breast cancer development. Therefore, suppressing the effects of the intended genes’ signature using myrrh extracts would provide encouraging results in blocking breast cancer tumorigenesis. Thus, our findings provide conclusive evidence and deepen the current understanding of the molecular role of myrrh in the treatment of breast cancer, further supporting its clinical application.